Discrete Dislocation Dynamics simulations of dislocation transport during sliding. (1st September 2018) - Gagel, J.; Weygand, D.; Gumbsch, P.
Abstract: Plastic deformation largely determines the properties of tribological contacts. To modify such contacts, it is thus necessary to understand the underlying mechanisms of dislocation motion and multiplication. In a sliding contact, dislocations do not only multiply, but also follow the moving tip — and are therefore "transported" by the tip. Three dimensional Discrete Dislocation Dynamics simulations of sliding with a spherical tip are conducted to analyse dislocation transport in an fcc crystal, at stresses below those typically required to nucleate dislocations at a free surface. Sliding direction, glide plane orientation and Burgers vector orientation determine whether a dislocation can be transported or not, and how far the transport leads. A model is proposed to identify the glide systems, on which dislocations are transported. Graphical abstract: Image 1